Pengelolaan Kearsipan di Dinas Perpustakaan dan Kearsipan Kota Sawahlunto - Delova, Lidya Sandra; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractThe paper discusses how the archival management of conventionally and electronically on the Office of the Department of libraries and Archives of the town of Sawahlunto. The purpose of the writing of this paper are: 1) describes the procedure for the management of the archives of the conventional and 2) describes the procedure for the management of electronic archives in the library and Archival service of the Office of the town of Sawahlunto.Â Â  Data collection methods used in this paper is a descriptive method of kualitatifpenemuan data is done through: (1) interviews with informants; (2) observation; (3) the study of librarianship through a variety of literature and documents relating to the issue of research. The informant of the research is the archivist and Office staff Office of Library and Archives of the town of Sawahlunto.Keywords: Management Of Archives